Lesion Development and Reperfusion Benefit in Relation to Vascular Occlusion Patterns after Embolic Stroke in Rats. Issue 2 (February 2014) - Bouts, Mark J R J; Tiebosch, Ivo A C W; van der Toorn, Annette; Hendrikse, Jeroen; Dijkhuizen, Rick M
Vascular occlusion sites largely determine the pattern of cerebral tissue damage and likelihood of subsequent reperfusion after acute ischemic stroke. We aimed to elucidate relationships between flow obstruction in segments of the internal carotid artery (ICA) and middle cerebral artery (MCA), and (1) profiles of acute ischemic lesions and (2) probability of subsequent beneficial reperfusion. Embolic stroke was induced by unilateral intracarotid blood clot injection in normotensive ( n =53) or spontaneously hypertensive ( n =20) rats, followed within 2 hours by magnetic resonance (MR) angiography (MRA), diffusion- (DWI) and perfusion-weighted magnetic resonance imaging (MRI) (PWI). In a subset of animals ( n =9), MRI was repeated after 24 and 168 hours to determine the predictive value of the occlusion pattern on benefit of reperfusion. The extent of cerebral perfusion and diffusion abnormality was related to the pattern of flow obstruction in ICA and MCA segments. Hypertensive animals displayed significantly larger cortical perfusion lesions. Acute perfusion-diffusion lesion mismatches were detected in all animals that subsequently benefitted from reperfusion. Yet, the presence of an angiography-diffusion mismatch was more specific in predicting reperfusion benefit. Combination of DWI, PWI, and MRA exclusively informs on the impact of arterial occlusion profiles after acute ischemic stroke, which may improve prognostication and subsequent treatment decisions.